ANALYSIS OF ANTHROPOMETRIC CHARACTERISTICS OF YOUNG MEN STUDYING AT A SPECIALIZED LYCEUM (Spectrum Journal of Innovation, Reforms and Development, 2022)
The article presents the results of experimental studies to identify the dynamics of anthropometric characteristics of students during their studies at a specialized lyceum.